Enantioselective Synthesis and in Vivo Evaluation of Regioisomeric Analogues of the Antimalarial Arterolane - Blank, Brian R. (J Med Chem, 2017)
[Image: see text] We describe the first systematic study of antimalarial 1,2,4-trioxolanes bearing a substitution pattern regioisomeric to that of arterolane. Conformational analysis suggested that trans-3″-substituted trioxolanes would exhibit Fe(II) reactivity and antiparasitic activity similar to that achieved with canonical cis-4″ substitution. The chiral 3″ analogues were prepared as single stereoisomers and evaluated alongside their 4″ congeners against cultured malaria parasites and in a murine malaria model. As predicted, the trans-3″ analogues exhibited in vitro antiplasmodial activity remarkably similar to that of their cis-4″ comparators. In contrast, efficacy in the Plasmodium berghei mouse model differed dramatically for some of the congeneric pairs. The best of the novel 3″ analogues (e.g., 12i) outperformed arterolane itself, producing cures in mice after a single oral exposure. Overall, this study suggests new avenues for modulating Fe(II) reactivity and the pharmacokinetic and pharmacodynamic properties of 1,2,4-trioxolane antimalarials.